2001
DOI: 10.1074/jbc.m104776200
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Structure of Natural Sterols and Sphingolipids on the Formation of Ordered Sphingolipid/Sterol Domains (Rafts)

Abstract: Ordered lipid domains enriched in sphingolipids and cholesterol (lipid rafts) have been implicated in numerous functions in biological membranes. We recently found that lipid domain/raft formation is dependent on the sterol component having a structure that allows tight packing with lipids having saturated acyl chains (Xu, X., and London, E. (2000) Biochemistry 39, 844 -849). In this study, the domain-promoting activities of various natural sterols were compared with that of cholesterol using both fluorescence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
211
3
4

Year Published

2003
2003
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 493 publications
(246 citation statements)
references
References 46 publications
22
211
3
4
Order By: Relevance
“…(i) In the presence of SM, replacement of cholesterol by ergosterol results in a membrane order that is as high as the order of membranes of the well characterized raft mixture SM/PC/cholesterol. This result confirms previous reports showing the property of ergosterol to have a condensing effect on glycerophospholipids (43)(44)(45)(46). (ii) Yeast PI increases the order of membranes containing IPC, irrespective of whether cholesterol or ergosterol is used as the sterol in these mixtures.…”
Section: Guvs From Yeast Total Lipid Extracts Showsupporting
confidence: 81%
“…(i) In the presence of SM, replacement of cholesterol by ergosterol results in a membrane order that is as high as the order of membranes of the well characterized raft mixture SM/PC/cholesterol. This result confirms previous reports showing the property of ergosterol to have a condensing effect on glycerophospholipids (43)(44)(45)(46). (ii) Yeast PI increases the order of membranes containing IPC, irrespective of whether cholesterol or ergosterol is used as the sterol in these mixtures.…”
Section: Guvs From Yeast Total Lipid Extracts Showsupporting
confidence: 81%
“…Such a result is somewhat surprising if one considers the very different efficiencies of sitosterol and stigmasterol in ordering phospholipid acyl chains of soybean phosphatidylcholine bilayers (40). However, the present results are entirely consistent with a recent work demonstrating a similar ability of both sitosterol and stigmasterol to promote domain formation (41).…”
Section: Figsupporting
confidence: 68%
“…We found that sphingomyelinase treatment augments the effect of cyclodextrin, consistent with the idea that stability of detergent-resistant domains requires both cholesterol and sphingomyelin. The cleavage product of sphingomyelin, ceramide, appears to be unable to substitute for the cleaved sphingomyelin, even though it strongly supports the formation of l o domains in model membranes (36). However, sphingomyelinase on its own did not reduce DRM association of the proteins tested, nor did it enhance the effect of saponin.…”
Section: Discussionmentioning
confidence: 88%